JALAN DAMAI PENYEBARAN TAREKAT NAQSHABANDIYAH MELALUI PONDOK PESANTREN (Studi Empiris di Majelis Dzikir Baitul Rahman Yogyakarta) - Paramitha Fazada; Bakhtiar Bakhtiar; Indah Eriyanti (Institut Teknologi Bisnis dan Kesehatan Bhakti Putra Bangsa Indonesia, 2023)
The teachings of pesantren cannot be separated from Sufism. Pesantren can be a center for gathering people who want to do wirid or suluk directly with kyai. However, not all pesantren can become centers of the Sufism movement (tarekat) in society. Only some pesantren are specifically the object of teaching Sufism The teachings of the Naqsabandiyah tariqah have the aim of forming a shaleh person by improving the quality of faith and pious taqwa so that it reaches the level of ma'rifat. The role of pesantren in spreading the naqsabandiyah tariqa to the community can be seen from the historical existence of the pesantren itself. Pesantren has become a community trust institution, so that people entrust the guidance of their life activities ranging from religious, social, cultural, political to economic to a kyai in pesantren. This paper aims to explain the existence of the Naqshabandiyah Order within the Islamic Boarding School. This research is a type of field research. The research was conducted in Bantul, Yogyakarta Data collection through interviews, observation and documentation. Data analysis was done descriptively by triangulation. The results showed that many naqsabandiyah tariqa teachings began with establishing pesantren, but there were also pesantren where a kyainya learned the tariqa and then taught it back to the students. In a sociological perspective, the Naqsabandiyah tariqa is able to be accepted in educational environments, especially Islamic boarding schools considering the direction of Naqshabandiyah in realizing human civilization, through the foundation or footing: creed; cult; code; and civilization.